1993
DOI: 10.1103/physreva.47.2827
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-electron removal and molecular fragmentation of CO by fastF4+impact

Abstract: Multiple-electron removal from and molecular fragmentation of carbon monoxide molecules caused by collisions with 1-MeV/amu F + ions were studied using the coincidence time-of-Aight technique. In these collisions, multiple-electron removal of the target molecule is a dominant process. Cross sections for the different levels of ionization of the CO molecule during the collision were determined. The relative cross sections of ionization decrease with increasing number of electrons removed in a similar way as see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 21 publications
5
25
1
2
Order By: Relevance
“…Note that a simple sum of the ionization potentials required for these ionized states shows 49.3 and 59.9 eV for (C 2+ , O + ) and (C + , O 2+ ), respectively. Table I also presents other experimental TOF data obtained by pulsed-beam coincidence methods in which individual charge-changing processes are not distinguished [1,11]. Their data of both production cross sections and branching ratios are in good agreement with each other irrespective of largely different incident species, velocities, and charges.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Note that a simple sum of the ionization potentials required for these ionized states shows 49.3 and 59.9 eV for (C 2+ , O + ) and (C + , O 2+ ), respectively. Table I also presents other experimental TOF data obtained by pulsed-beam coincidence methods in which individual charge-changing processes are not distinguished [1,11]. Their data of both production cross sections and branching ratios are in good agreement with each other irrespective of largely different incident species, velocities, and charges.…”
Section: Resultsmentioning
confidence: 54%
“…In the last few decades collision-induced molecular fragmentation was extensively studied for various combinations between projectile particles and molecules [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The investigation was carried out for the identification of fragment-ion pairs, kinetic energies of the fragments, and the orientation effect on the molecular fragmentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electron impact mass spectrum of CO gas shows a dominant CO ϩ peak, followed by three peaks of about the same intensity: C ϩ , O ϩ , and CO 2 ϩ [24]. The fragmentation of CO by 1 MeV/u F 4ϩ ions has CO ϩ as the main final product, followed by the C ϩ ϩ O 0 and C 0 ϩ O ϩ by channels with cross sections 6 to 7 times of magnitude lower [25], whereas 2.4 MeV/u Ar 14ϩ projectiles result in cross sections about 3 to 5 times lower [26]; C ϩ and C 2ϩ ion production is enhanced with respect to O ϩ and O 2ϩ , respectively. For CO 2 dissociation after collision with 3.6 MeV/u Si 8ϩ projectiles, it was reported that the peripheral O ions have larger kinetic energies than the central C ions [27].…”
Section: Discussion Of Ion Formationmentioning
confidence: 99%
“…(4)], is usually the dominant dissociative ionization channel (see, e.g., the review by Codling and Frasinski [68] and Refs. [33,44,[69][70][71][72][73]). The latter, in contrast, has an asymmetric charge state distribution [CAD; see Eq.…”
Section: B Charge Asymmetric Dissociation (Cad)mentioning
confidence: 99%